Cryptic within cryptic: genetics, morphometrics, and bioacoustics delimitate a new species of Eleutherodactylus (Anura: Eleutherodactylidae) from Eastern Cuba - Rodríguez, Ariel; Dugo-Cota, Álvaro; Montero-Mendieta, Santiago; Gonzalez-Voyer, Alejandro; Bosch, Roberto Alonso; Vences, Miguel; Vilà, Carles (Zootaxa, 2017)
We studied the variation in genetics, bioacustics, and morphology in Eleutherodactylus glamyrus, a regionally endemic frog species restricted to high elevations in the Sierra Maestra Massif, Western Cuba that was originally described as a cryptic species hidden under the name E. auriculatus. Genetic analysis of mtDNA sequences of the 16S and cob genes identify two allopatric and strongly supported mitochondrial clades (phylogroups) which also showed no haplotype sharing in the nuclear Rag-1 gene. Bioacustic, and morphological comparisons concordantly identify these two phylogroups as independent evolutionary lineages. Therefore, we herein restrict the name Eleutherodactylus glamyrus Estrada and Hedges to populations represented in our analyses as the western phylogroup (Cordillera del Turquino to Pico La Bayamesa) and consider specimens from the eastern phylogroup (Sierra del Cobre) to represent a new species described and named as Eleutherodactylus cattus. Our results add to the growing list of Eleutherodactylus species endemic to Cuba and highlight the importance of combining different sources of evidence for obtaining robust assessments of species limits in amphibians.